Algoritma FIFO Untuk Pengendalian Stok Pada Aplikasi Inventory Obat Berbasis Web - Ricky Andri Widayat; Agung Triayudi; Ben Rahman (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
One of the factors causing errors in inventory is the lack of a support system for processing drug sales. Data processing of sales, purchases, and drug supplies is still done manually. This causes medicines to be stored in warehouses for too long or even expired. The web-based drug inventory application is designed to speed up the work process and overcome these problems. This design uses PHP, CSS, HTML, JavaScript, XAMPP, and MySQL Workbench programming languages. This study aims to simplify drug stock control, apply the FIFO algorithm for organized distribution, and produce structured and easy-to-find reports. This research uses PHP language and MySQL database. The software used is Sublime and HeidiSQL. The results of the study indicate that the drug inventory application created can facilitate storage activities